Pengaruh Pemberian Serbuk Simplisia Andrographys Paniculata Nees Terhadap Hasil 6-Mwt (Six Minute Walking Test), Dan Hba1c Pada 5 Penderita Xiao Ke Kronik (Dmt2 Kronik) Di Kedai Jamu Citra, Tangerang - Sumanto Hadi (Sekolah Tinggi Agama Buddha Nalanda, 2020)
with the unwittingness of the sufferer who often has both visible and unseen major complaints, 3 lots (eating, drinking, urinating) 1 less (decrease weightless cause). The way Ap works with the main substance andrographolide to reduce sugar in the blood, as a metabolic enhancement of blood sugar profiles. Bitter, cold, sedating and decreasing, cooling heat (antipyretics), offering toxins (anti-inflammatory), removing moist (diuretics), especially the lungs, stomach, and bladder. The characteristics of Xiao Ke Kronik: insufficiency/deficiency of Qi and Yin that deficiency of Energy / Qi found in exogenous functional fatigue (6-MWT) is not effective and efficient enough to increase fatigue, to decrease HbA1c in patients with chronic or endogenous Yin deficiency, TCM, Yin is more difficult because it is chronic (HbA1c). This type of research is a quantitative experiment and as an exploratory observational study, by recording the results of the 6-MWT and HbA1c tests before and after the study. The results of the study were not statistically significant on the 6-MWT test results and HbA1c reduction in chronic Xiao to patients (chronic DMT2).